1997
DOI: 10.1159/000190321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>L</i>-Histidinol on Cisplatin Nephrotoxicity in the Rat

Abstract: The effect of L-histidinol (LHL) on the acute nephrotoxicity produced by cisplatin (CDDP; 6 mg/kg, i.v.) was investigated in the rat. Intraperitoneal administration of LHL (100 mg/kg × 5 doses, 2 h apart) starting 2 h prior to CDDP single injection produced significant protection of renal function. The attenuation of nephrotoxicity was evidenced by significant reductions in serum urea and creatinine concentrations, decreased polyuria, reduction in body weight loss, marked reduction in urinary fractional sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The finding that LHL attenuates IFO-induced FS in rats is in harmony with the results obtained by Badary et al [14]who demonstrated a protective effect of LHL on cisplatin-induced nephrotoxicity in rats. Moreover, the present data are supported by earlier findings of Edelstein [25]who demonstrated a protective effect of LHL on cisplatin-induced hematopoietic toxicity in mice and those of Sawyer et al [26]who showed that LHL protected mice from fluorouracil-induced toxicity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding that LHL attenuates IFO-induced FS in rats is in harmony with the results obtained by Badary et al [14]who demonstrated a protective effect of LHL on cisplatin-induced nephrotoxicity in rats. Moreover, the present data are supported by earlier findings of Edelstein [25]who demonstrated a protective effect of LHL on cisplatin-induced hematopoietic toxicity in mice and those of Sawyer et al [26]who showed that LHL protected mice from fluorouracil-induced toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Whether LHL will achieve beneficial effects in the clinical situation remains to be demonstrated. However, the effectiveness of oral LHL against IFO toxicity shown here and the recent prior data suggesting benefit during cisplatin [14]and doxorubicin [13]treatment indicate that further consideration may be given to the clinical application of this approach to reduce the toxicity associated with cancer chemotherapy.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The exact mechanism of nephrotoxicity induced by CP is not fully understood and is still controversial, but it has been sometimes associated with renal lipid peroxidation [9]. The period after which a single dose of CP can induce nephrotoxicity in rat model is different ranging from 1 up to 7 days as reported by several investigators [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in animals, melatonin [11], 4-methylthiobenzoic acid [12], L-histidine [10], and the flavonoid silibinin [14] have been shown to reduce CP-induced nephrotoxicity. However, none of them has proven to be clinically effective as a complete protective agent in patients.…”
Section: Introductionmentioning
confidence: 99%